Self-perception of ethically dubious practices: a study with Human Resource managers - Simões, E.; Duarte, A.P.; Silva, V. H.; Neves, J. (18th congress of the European Association of Work and Organizational Psychology, 2017)
Currently, most organizations assume corporate social responsibility as an important purpose, and ethical scrutiny in all areas of organizational life is seen as a natural consequence of this option. However, practices and the currently prevailing discourse of Human Resources Management (HRM) seem to ignore those concerns. Emphasis on strategic alignment has led HRM’s agents to focus primarily on organizational rationality and control, highlighting the importance of HRM to corporate profitability, preferring thereby to distance themselves from a certain humanistic matrix of HRM’s historical origins. The main goal of the present study with HR managers ( N=149) was to examine the acceptability of ethically dubious HRM practices, taking into account the existence and the practical salience of ethical infrastructure (e.g., codes of conduct, compliance and ethics programs) and the perception of corporate social responsibility practices in their organizations. The degree of practical salience given to ethical infrastructures predicts the acceptability level of ethically dubious practices, with participants from high salience organizations judging the practices of personal disregard as more acceptable than those of discrimination and power favoring. HRM discrimination practices are also less acceptable to the participants from organizations that are perceived as more responsible in any CSR dimensions (economic, community and internal). Power favoring practices in HRM tend to be less acceptable to those working in organizations considered more socially responsible economically. Practical implications of the overall results for the enhancement of ethicality of HRM practices are discussed.